Association of systemic immune-inflammatory index with stress urinary incontinence in U.S. Adults: NHANES 2007–2016 - Sijia Ma; Linlin Qian; Yuhua Jiang; Meng Wang; Shijie Xu; Chao Wang (PLoS ONE, 2026)
Background The aim of this study is to explore the association between the systemic immune-inflammatory index (SII) and stress urinary incontinence (SUI). Methods We used information obtained from the National Health and Nutrition Examination Survey (NHANES) that was conducted between 2007 and 2016. The weighted multivariate logistic regression model was used in order to evaluate the relationship that exists between the SII index and the SUI measurement. In addition, a technique from the field of smooth curve fitting was used to investigate the linear connection that exists between these variables. In order to determine whether or not the SII index and SUI relationship remained stable across a variety of demographic strata, subgroup analyses were carried out. Results The research had a grand total of 20,849 individuals. After full adjustment for confounders, each 1-unit increase in log₁₀(SII) was associated with a 29.7% increase in the odds of SUI (OR=1.297, 95%CI 1.028–1.636, P = 0.032). Categorizing the SII index into quartiles revealed that even in the highest SII quartile, there remained a significant positive association with SUI when compared to the lowest quartile (OR =1.177, 95%CI 1.013–1.368, P = 0.038). Furthermore, an augmented correlation between alcohol consumption and SUI was detected among drinkers compared to non-drinkers ( P < 0.05). Conclusions Higher systemic inflammatory burden reflected by SII is statistically significantly associated with increased odds of SUI in the U.S. adult population, though the effect size is small; this association is particularly prominent in alcohol drinkers.